The future of diversity - Kuptsch, Christiane; Charest, Éric (International Labour Organization, 2021)
In this collection, scholars and practitioners reflect on the most appropriate interventions to create a more inclusive labour market for all. They explore the economic case for diversity and diversity management strategies, finding that diversity and inclusion must go hand in hand. The book also sheds light on the policy dilemma between respecting individuals and countering structural inequalities, which often requires categorization into groups. The authors remind us that there is diversity within diversity: not everyone receiving the same label has the same needs. The book covers a range of issues including gender equality and mainstreaming, migration and ethnic diversity, racism, violence against LGBTI people and age discrimination. It is thus a rich source of inspiration for anyone wishing to move towards greater justice in the labour market.
Keywords: approches et analyses; discipline; identités LGBTQIA2+; inégalités; justice sociale; racisme; rapport; sciences de la gestion; sexisme; systèmes d'oppressions; thématiques; économie

L’économie solidaire sous le prisme du genre: une analyse critique et possibiliste - Guérin, Isabelle; Hillenkamp, Isabelle; Verschuur, Christine (Revue Française de Socio-Économie, 2019)
Cet article propose d’étudier l’économie solidaire sous le prisme du genre à partir d’un double regard, critique et possibiliste. Ce double regard, inspiré à la fois de l’économie substantive polanyienne et des recherches féministes, éclaire la manière dont les pratiques d’économie solidaire renouvellent l’économique et le politique, compris ici à la fois comme catégories d’action et de pensée. Il met aussi en lumière les chemins multiples et sinueux de l’émancipation, fruit d’un entremêlement entre principes d’échange dont l’équilibre est en renouvellement permanent.
https://rfse.univ-lille.fr
Keywords: OFDIG; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; pouvoir; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; économie; économie solidaire

Gender and development - Rai, Shirin M. (Handbook on the international political economy of gender, 2018)
Keywords: LGBTQIA2+; OFDIG; approches et analyses; discipline; finance; genre; identités LGBTQIA2+; intersectionnalité; inégalités; sciences de la gestion; sofia; systèmes d'oppressions; thématiques; économie; égalité des sexes

How (the meaning of) gender matters in political economy - Peterson, Spike V. (New Political Economy, 2005)
Keywords: OFDIG; approches et analyses; discipline; genre; identités LGBTQIA2+; inégalités; ressource en ligne; sciences de la gestion; systèmes d'oppressions; thématiques; économie